2010
DOI: 10.1051/0004-6361/201014606
|View full text |Cite
|
Sign up to set email alerts
|

Star formation in AGN hosts in GOODS-N

Abstract: Sensitive Herschel far-infrared observations can break degeneracies that were inherent to previous studies of star formation in high-z AGN hosts. Combining PACS 100 and 160 μm observations of the GOODS-N field with 2 Ms Chandra data, we detect ∼20% of X-ray AGN individually at >3σ. The host far-infrared luminosity of AGN with L 2−10 keV ≈ 10 43 erg s −1 increases with redshift by an order of magnitude from z = 0 to z ∼ 1. In contrast, there is little dependence of far-infrared luminosity on AGN luminosity, for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
179
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 174 publications
(221 citation statements)
references
References 25 publications
37
179
5
Order By: Relevance
“…Compared to previous attempts from the submm (e.g., Lutz et al 2010) and Spitzer (e.g., Mullaney et al 2010), Herschel performance provides a big step forward. Shao et al (2010) use the PEP GOODS-N observations and the Chandra Deep Field North to map out the host star formation of AGN of different redshifts and AGN luminosities. The host far-infrared luminosity of AGN with L 2−10 keV ≈ 10 43 erg s −1 increases with redshift by an order of magnitude from z = 0 to z ∼ 1, similar to the increase with redshift in the star formation rate of inactive massive galaxies.…”
Section: Agn-host Coevolution: Two Modes?mentioning
confidence: 99%
“…Compared to previous attempts from the submm (e.g., Lutz et al 2010) and Spitzer (e.g., Mullaney et al 2010), Herschel performance provides a big step forward. Shao et al (2010) use the PEP GOODS-N observations and the Chandra Deep Field North to map out the host star formation of AGN of different redshifts and AGN luminosities. The host far-infrared luminosity of AGN with L 2−10 keV ≈ 10 43 erg s −1 increases with redshift by an order of magnitude from z = 0 to z ∼ 1, similar to the increase with redshift in the star formation rate of inactive massive galaxies.…”
Section: Agn-host Coevolution: Two Modes?mentioning
confidence: 99%
“…Different observations now question that BH-host correlations indeed appear as tight as previously claimed for all types of galaxies (e.g., Hu 2008;Graham 2008;Gültekin et al 2009;Graham & Li 2009). Significant outliers exist (e.g., Mathur et al 2001;Grupe & Mathur 2004;Watson et al 2007), BHs are currently observed also in the centres of bulgeless galaxies (e.g., Ghosh et al 2008;Satyapal et al 2009;Araya salvo et al 2012), and the AGN-starformation correlations disappear for all but highest luminosity AGNs (Shao et al 2010;Grier et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Already, observations from Herschel have been used to great effect to investigate the relationship between various types of AGN and their starbursting host galaxies. In galaxies with X-ray-selected AGN, numerous studies have found correlations between the strength of the starburst in galaxies, as determined by Herschel, and the strength of the AGN they host (Shao et al 2010;Harrison et al 2012b;Rovilos et al 2012;Santini et al 2012; though for an alternative viewpoint see Page et al 2012). The host galaxies of radio-and IR-selected AGN have also been the subjects of investigation with Herschel (e.g., Hardcastle et al 2012;Del Moro et al 2013), though the connection between these AGNs and their host galaxies is less clear than in the case of X-ray-selected AGN.…”
Section: Introductionmentioning
confidence: 99%